Treatment of Produced Water by Bioadsorption Technology: Removal of Copper from Petroleum Industry - Ranjan, Abhishek; Chandanasri, P; Sahu, Omprakash (Journal of Advanced Research in Petroleum Technology & Management; Vol 6 No 1&2 (2020): Journal of Advanced Research in Petroleum Technology and Management, 2021)
Oil and gas industry is considered as the most hazardous and polluting industry among all. Numerous pollutants generated during the processing of the oil and gas industry. In that produced water is a major concern to bring up to acceptable norms. Heavy metals produced from industrial wastewater has become concerned about environmental life today. Various studies have been done for the removal of heavy metals. The treatment of wastewater has become expensive. The objective of research work is to treat the petroleum industry wastewater (heavy) with bio-adsorbent (wooden bark). The experiment was carried out in batch mode to optimize various operating parameters. The results show a maximum of 90% of copper can be removed at optimum condition. At last, it is recommended that the bioabsorption method is economical and convenient to employ in the petroleum industry.